A Study of The Radionuclides of The Petroleum Waste In Dora and Bijie Refineries Using (Hpge) Detector - Rasheed , Essam Mohammed (Journal of Petroleum Research and Studies, 2012)
The aim of this study is to detect the radioactivity of radionuclides and measure the specific activities and the uranium concentration in (19) samples of crude oil and oil waste were brought from two oil locations Dora refinery, Bijie refinery. The measurements in this study were done by using two techniques: 1- Gamma rays spectroscopy system was used to measure the specific activity for radionuclides. This system is consist of high purity of germanium detector (HPGe) with personal computer as multi channel analyzer (MCA) that computerized to plot the radioactive spectrum and compute the specific activities of the radionuclides. There are seven radionuclides are detected: (Bi-214, Ra-226, TI-208, Bi-212, Pb-212, K-40, and Cs-137), these radionuclides included; two radionuclides (Bi-214,Ra-226) belong to the U-238 series, three radionuclides (TI-208, Bi-212, Pb-212) belong to Th-232series, one natural radionuclide (K-40), and one artificial radionuclide (Cs-137). For Dora refinery samples, the averages of specific activities of (Bi-214, Ra-226) were (7.79, 16.08) Bq/kg respectively, the averages of specific activities of (TI-208, Bi-212, Pb-212) were (7.95,4.05,5.75) Bq/kg , the average of specific activities of (Cs-137) was (0.64) Bq/kg , the average of specific activities of (K-40) was (99.3) Bq/kg. For Bijie refinery samples, the average of specific activities of (Bi-214) was (0.39) Bq/kg, the averages specific activities of (Bi-212, Pb-212) were (0.02,0.01) Bq/kg, the average of specific activities of (K-40) was (2.28) Bq/kg , and three radionuclides (Ra-226, TI-208, and Cs-137) were not appeared in Bijie samples. 2- solid state nuclear track detectors technique (SSNTDs), the uranium concentration determined by using CR-39 track detector and fission fragment track technique, the nuclear reaction used as source of uranium fission fragment is U-235 (n-f) obtained by the bombardment of U-235with thermal neutrons emitted from (Am-Be) neutron source with flux (5000 n/cm2.s) for seven days, the concentration were calculated by comparison with the standard samples. The uranium concentration in Dora refinery samples were ranged between (0.95-3.34) ppm with average (2.03) ppm for solid samples and (1.25) ppm for liquid samples. The uranium concentration in Bijie refinery samples were ranged from (0.42-1.46) ppm with average (0.55) ppm in the solid samples and (1.24) ppm in the liquid samples, these results are agreement with the permissible limit from IAEA, the permissible limit is (1mSv/y) for the public.